2011
DOI: 10.1002/ejoc.201101409
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biaryls through a One‐Pot Tandem Borylation/Suzuki–Miyaura Cross‐Coupling Reaction Catalyzed by a Palladacycle

Abstract: The tricyclohexylphosphane adduct of cyclopalladated ferrocenylimine I exhibited high catalytic activity in the one‐pot borylation/Suzuki–Miyaura coupling (BSC) reaction with low catalyst loading (2 mol‐%). Various biaryls were obtained in good to excellent yields for 37 examples. This process was applied to aryl and heteroaryl halides (Br and Cl) containing a variety of functional groups and did not require an excess amount of phosphane ligand and the addition of the palladium catalyst in the second step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Since the discovery of the one‐pot borylation–Suzuki sequence, there has been a steady development of various methods and catalysts which have improved performance and scope . Cui and Wu et al . showed that efficient borylation–Suzuki coupling of heteroaryl bromides could be obtained by using a ferrocenylimine‐palladacycle at 2 mol% of Pd, without the need of additional ligand.…”
Section: Figurementioning
confidence: 99%
“…Since the discovery of the one‐pot borylation–Suzuki sequence, there has been a steady development of various methods and catalysts which have improved performance and scope . Cui and Wu et al . showed that efficient borylation–Suzuki coupling of heteroaryl bromides could be obtained by using a ferrocenylimine‐palladacycle at 2 mol% of Pd, without the need of additional ligand.…”
Section: Figurementioning
confidence: 99%
“…Alternatively, I can also be converted to the corresponding boronic ester IV and subsequently be coupled with 2-chloro-pyridine or its derivatives to introduce the R 1 group at the C5 of the pyrimidine ring. 12 Overall, this route is optimal to explore the structure-activity relationship (SAR) at the R 1 site; it can also be used for SAR exploration at the R 2 and R 3 sites.…”
Section: Chemistrymentioning
confidence: 99%
“…Some useful recent examples include the work of Wang et al [157], which involved a one-pot borylation/Suzuki-Miyaura reaction. Some useful recent examples include the work of Wang et al [157], which involved a one-pot borylation/Suzuki-Miyaura reaction.…”
Section: Recent New Developments 67mentioning
confidence: 99%